ANALISIS MOTIVASI EKSTRINSIK SISWA DI SDN INTI LAMPASIO - Nur Azizah; Ikbal (Jurnal Teknologi Pendidikan Madako, 2025)
This study aims to analyze and identify the forms of extrinsic motivation applied by teachers to fifth-grade students at SDN Inti Lampasio. The research employed a descriptive qualitative approach with the subjects consisting of fifth-grade students and their class teacher. Data collection techniques included observation, interviews, and documentation, while data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal five forms of extrinsic motivation used by the teacher: (1) giving grades or scores, (2) providing rewards, (3) applying educational punishments, (4) giving praise, and (5) providing feedback on learning outcomes. These five forms of motivation were proven to enhance students’ learning enthusiasm, discipline, active participation, and self-confidence. Students responded positively to the strategies implemented by the teacher and showed constructive behavioral changes. The application of extrinsic motivation also aligns with behavioristic and social reinforcement theories, which state that external stimuli can strengthen students’ learning behavior. Thus, extrinsic motivation plays a crucial role in encouraging student engagement in elementary school learning.